The Role of Law Enforcement in Overcoming Corruption Crimes in the Form of Bribery by Civil Servants - Hutabarat, Hendrik Sout Parningotan; Siregar, Taufiq; Akmal, M. Ridha H. (Journal La Sociale, 2025)
Corruption, especially bribery by civil servants (PNS), is a serious problem that threatens the integrity of the government system in Indonesia. Law enforcement in overcoming corruption is very important in order to realize a clean government and free from abuse of authority. The purpose of this study is to analyze the role of law enforcement in eradicating corruption in the form of bribery involving civil servants. This study uses an analytical descriptive approach by examining existing regulations, the role of law enforcement officials, and challenges in implementing law enforcement against civil servants involved in bribery. The results of the study show that despite strict regulations, law enforcement against civil servants involved in bribery practices still faces various obstacles, such as weak internal supervision and the potential for conflicts of interest. Therefore, it is necessary to increase cooperation between law enforcement agencies, such as the Corruption Eradication Commission (KPK), the Police, and the Prosecutor's Office, to strengthen the supervision mechanism and take firm action against corrupt actors. This research is expected to contribute to increasing the effectiveness of corruption eradication in Indonesia.